Tiwi's Creek: Indigenous Movements for, Against, and Across the Contested Peruvian Border - Greene, Shane (Latin American and Caribbean ethnic studies, 2008)
This article analyzes the impact of the long-standing Peru/Ecuador border dispute on the indigenous politics of the border region. The ethnic groups occupying the area are engaged in a bi-national struggle to contest dominant representations suggesting that the 1998 Peace Accord has led to the final territorial enclosure of the two nation-states. At the same time, the leaders of the indigenous groups must confront their own intra-ethnic 'border' problems. The question of how to represent these struggles remains the subject of intense debates. Internal differences in the use of ethnonyms (particularly the central term 'Jivaro') reveal that indigenous politics are already over-determined by the colonial past and present of both Peru and Ecuador.